Verses for the Dead : Pendergast #18 - Preston, Douglas J.; Child, Lincoln (New York : Grand Central Publishing, 2018)
Forced by an overhaul of leadership to accept a partner, FBI Special Agent Pendergast and his new teammate, junior agent Coldmoon, investigate a rash of gruesome killings by a psychopath who cuts out the hearts of his victims and leaves them at local gravestones.
Keywords: Pendergast, Aloysius -- (Fictitious character) -- Fiction; Pendergast, Aloysius -- (Fictitious character) -- Fiction; Government investigators -- Fiction; Serial murder investigation -- Fiction; Governmental investigations -- Fiction; Serial killers -- Fiction; Criminal investigation -- Fiction; Suspense fiction; Mystery fiction